Pemisahan Yurisdiksi Pengadilan Pajak Pasca Putusan MK No. 26/PUU-XXI/2023 - Cassis Merinthia Ariapramuda; Atiek Pratiwi Putri Naue; Irwan Triadi; Mas Pungky Hendra Wijaya (Lembaga Yasin AlSys, 2026)
Taxes play a vital role as the backbone of fiscal sovereignty that ensures the sustainability of national development. However, the institutional position of the Tax Court under the executive branch has long created ambiguity and doubts regarding judicial independence for justice seekers. This study aims to analyze the institutional problems of the Tax Court and the implications of Constitutional Court Decision Number 26/PUU-XXI/2023 for strengthening the independence of the tax judiciary in Indonesia. This study employed a normative legal research method with statutory and conceptual approaches, which were analyzed descriptively-analytically based on secondary legal materials. The results showed that the Constitutional Court’s decision has ended the unconstitutionality of the dual supervisory system by placing the Tax Court entirely under the Supreme Court. This transformation changes the institutional paradigm from an executive regime to a purely judicial regime in order to reduce the potential for conflicts of interest and bureaucratic bias in the trial process. This study emphasizes that the implementation of a one-roof system is an important model for realizing legal certainty, strengthening judicial independence, and increasing trust in Indonesia’s taxation system. In addition, strengthening the dignity of the tax judiciary needs to be followed by the effectiveness of decision enforcement so that tax justice does not stop at the pronouncement of the ruling, but also provides a tangible impact for taxpayers.